Legally blonde [videorecording (DVD)] - Luketic, Robert, 1973-; Witherspoon, Reese, 1976-; Wilson, Luke, 1971-; Blair, Selma, 1972-; Davis, Matthew, 1978-; Garber, Victor; Coolidge, Jennifer; Taylor, Holland; Larter, Ali, 1976- (MGM Home Entertainment, 2001)
When a blonde sorority queen is dumped by her boyfriend, she decides to follow him to law school to get him back and, once there, learns she has more legal savvy than she ever imagined.